Top of mind use content to unleash your influence and engage those who matter to you - Hall, John (McGraw-Hill Education, 2017)
A step-by-step guide showing you how to use content to keep your brand front and center; this invaluable book will help you position yourself for success by establishing and developing content-driven relationships that keep you and your brand Top of Mind. --